Improving Skills of Writing Observation Report Texts Using Project-Based Learning (PjBL) Method in Grade X Students of SMA Negeri 1 Jangka Buya Pidie Jaya - Ira Munira; Nurlaili; Rahmi, Hayatun (KIRANA : Social Science Journal, 2025)
This study entitled "Improving Writing Skills of Observation Report Text Using Project Based Learning (PJBL) Method for Grade X Students of Sma Negeri 1 Jangka Buya, Pidie Jaya Regency" raises the problem of How to improve writing skills of observation report text through Project Based Learning (PJBL) model in Grade X students of Sma Negeri 1 Jangka Buya. This study aims to describe the improvement of writing skills of observation report text through Project Based Learning (PJBL) model in Grade X students of Sma Negeri 1 Jangka Buya. This study is a descriptive study with qualitative approach. The approach in this study was taken because the researcher wanted to describe and get an overview related to improving writing skills of observation report text through Project Based Learning (PJBL) model in Grade X students of Sma. Data collection in this study used 3 (three) techniques, namely Observation, Interview and Documentation Study and added with a test of students' abilities that were given previous understanding. The results of the observation showed that students played an active role in improving writing skills of observation report text. The results of the material test (written test) showed an average score obtained by students of 82.3 with a KKM standard of 70. In answering the essay questions given, on average students were not only able to mention, but were also able to explain even in their own language. This shows that students not only remember the material given but also understand it. The results of interviews conducted with three informants from students concluded that the audio-visual media involved in drama learning helped them understand the material and provided a different learning experience.